First Reported Case of Lorazepam-Assisted Interview in a Young Indian Female Presenting with Dissociative Identity Disorder and Improvement in Symptoms after the Interview - Raheel Mushtaq; Sheikh Shoib; Tasleem Arif; Tabindah Shah; Sahil Mushtaq (Case Reports in Psychiatry)
Dissociative identity disorder (DID) is one of the most fascinating disorders in psychiatry. The arduous search to reveal the obscurity of this disorder has led to colossal research in this area over the years. Although drug-assisted interviews are not widely used, they may be beneficial for some patients that do not respond to conventional treatments such as supportive psychotherapy or psychopharmacotherapy. Drug-assisted interviews facilitate recall of memories in promoting integration of dissociative information. We report a case of a 16-year-old female with dissociative identity disorder (DID) that was treated with lorazepam-assisted interview and there was rapid improvement in symptoms after the interview.